Synthesis and Docking Studies of Novel Triazole Derivatives as Potential Breast Cancer Therapeutics - Manisha Veer, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Breast cancer remains a leading cause of cancer-related mortality among women worldwide. The development of novel therapeutics is critical to improve patient outcomes. This study focuses on the synthesis of novel triazole derivatives and evaluates their potential as breast cancer therapeutics through molecular docking studies. Introduction: Despite advancements in breast cancer treatment, new therapies are needed due to resistance and side effects of current options. Triazole derivatives are promising due to their diverse biological activities. This research aims to synthesize new triazole derivatives and assess their potential against breast cancer through molecular docking studies. Methods and Materials: Triazole derivatives were synthesized via refluxing substituted phenyl hydrazine with ethyl acetoacetate, followed by cyclization with triethyl orthoformate. The compounds were characterized using NMR, IR, and MS. Molecular docking was performed using AutoDock Vina against HER2 and ERα proteins, with interactions visualized and analyzed using PyMOL. Results: The synthesized triazole derivatives were obtained in high yields (70-85%) and purity (>95%). NMR, IR, and MS confirmed the expected structures. Docking studies revealed strong binding affinities ranging from -8.5 to -10.2 kcal/mol with HER2 and ERα, with key interactions including hydrogen bonding, π-π stacking, and hydrophobic interactions. The docking scores were comparable to or better than known inhibitors.